The Impact of Physical Activity on Disability Incidence among Older Adults in Mexico and the United States - Kerstin Gerst; Alejandra Michaels-Obregon; Rebeca Wong (Journal of Aging Research)
Evidence suggests that transitions among older adults towards healthy habits, such as physical activity, appear underway in developed countries such as the USA but not in developing countries such as Mexico. However, little is known about the potential benefit of physical activity in preventing disability among elders in countries at different stages of epidemiological transition. We explore the impact of physical activity on the disablement process among elders in Mexico compared to the USA. Data are from two waves of the Mexican Health and Aging Study and the Health and Retirement Study. We examine the impact of exercise on the transition from no disability to ADL limitations two years later. Findings indicate that exercise is more common in the U.S. than in Mexico. There is a positive effect of exercise on negative outcomes in both countries. However, the protective effect of exercise is stronger in the U.S. than in Mexico.